Effects of levamisole on normal and abnormal leukocyte locomotion. - D G Wright; C H Kirkpatrick; J I Gallin (The Journal of Clinical Investigation, 1977)
The anti-helminthic drug levamisole hydrochloride has been reported to stimulate immune responses in humans and experimental animals. We have investigated levamisole effects on human leukocyte locomotion in vitro in studies of neutrophils and mononuclear cells from normal adults, from patients with Chediak-Higashi disease and from patients with the syndrome of hyperimmunoglobulin E, recurrent pyogenic infections, and defective leukocyte chemotaxis. Directed migration (chemotaxis) of neutrophils and mononuclear cells from normal adults and from the hyperimmunoglobulin E syndrome patients, but not from Chediak-Higashi patients, were stimulated by levamisole at concentrations of 0.01-1.0 micronM, with stimulation observed most consistently at 0.1 micronM. These concentrations of drug also increased cyclic GMP levels in mononuclear cells and enhanced hexose monophosphate shunt activity in neutrophils, but did not alter chemotactic factor-induced changes in the surface charge of neutrophils. Other concentrations of levamisole did not affect leukocyte locomotion except for a high concentration (5.0 mM) which stimulated both random and directed leukocyte migration. When patients with the hyperimmunoglobulin E syndrome took levamisole by mouth, the abnormal chemotactic responses of their neutrophils were significantly improved towards normal. These studies are the first to show pharmacologic improvement of in vitro leukocyte locomotion in patients in whom recurrent infections have been attributed to a defect of this leukocyte function.